Studi Literatur : Analisis Penyediaan Ruang Terbuka Hijau di Wilayah Urban - Meirina Wahyu Purnamaselfi; Hasti Widyasamratri (Universitas Islam Sultan Agung, 2022)
ABSTRACTGreen open space is one of the noteworthy lists in development planning and implementation. The existence of green open space will increase the quality of urban ecology. In accordance with Minister of Public Works Regulation No. 05 / PRT / M / 2008 concerning Guidelines for Provision and Utilization of Green Open Space in Urban Areas, the ideal area of green open space in urban areas is 30% consisting of 10% private green open space and 20% public open green space from the city area. The effort to make this happen is by determining and revitalizing public green open space. Damaged green open space needs to be a concern of the government because it can reduce the aesthetics and function of the environment. The use of the method for writing this research is a method of literature study obtained from books and journals with locations : Kartasura District, Martapura, East Palu District,. The outputs of this study conclude that the requisite and existence of green open space in several cities that still do not meet the broad percentage contained in the regulations so that development planning needs to optimize areas that have the potential for the determination of green open space.Keywords : Provision, Green Open Space, Urban. ABSTRAKRuang terbuka hijau merupakan salah satu daftar penting dalam perencanaan dan pelaksanaan pembangunan. Adanya ruang terbuka hijau akan meningkatkan kualitas ekologi perkotaan. Sesuai Peraturan Menteri Pekerjaan Umum No. 05/PRT/M/2008 tentang Pedoman Penyediaan dan Pemanfaatan Ruang Terbuka Hijau di Kawasan Perkotaan, luasan ideal RTH di perkotaan adalah 30 % yang terdiri dari 10 % RTH privat dan 20 % RTH publik dari luas kota. Usaha untuk mewujudkannya adalah dengan cara penetapan dan revitalisasi RTH publik. Ruang terbuka hijau yang rusak perlu menjadi perhatian pemerintah karena dapat mengurangi estetika dan fungsi lingkungan. Penggunaan metode untuk penulisan penelitian ini adalah metode studi literatur yang diperoleh dari buku dan jurnal dengan lokasi di Kecamatan Kartasura, Martapura, dan Kecamatan Palu Timur. Hasil dari kajian ini menyimpulkan bahwa kebutuhan dan keberadaan RTH di beberapa kawasan kota yang ada masih belum memenuhi presentase luas yang terdapat dalam peraturan sehinngga perencanaan pembangunan perlu mengoptimalkan wilayah yang memiliki potensi untuk penetapan RTH.Kata kunci : Penyediaan, Ruang Terbuka Hijau, Urban.